Sacrificial Cu Layer Mediated the Formation of an Active and Stable Supported Iridium Oxygen Evolution Reaction Electrocatalyst - Lončar, Anja; Escalera-López, Daniel; Ruiz-Zepeda, Francisco; Hrnjić, Armin; Šala, Martin; Jovanovič, Primož; Bele, Marjan; Cherevko, Serhiy; Hodnik, Nejc (ACS Catalysis, 2021)
The production of hydrogen via a proton-exchange membrane water electrolyzer (PEM-WE) is directly dependent on the rational design of electrocatalysts for the anodic oxygen evolution reaction (OER), which is the bottleneck of the process. Here, we present a smart design strategy for enhancing Ir utilization and stabilization. We showcase it on a catalyst, where Ir nanoparticles are efficiently anchored on a conductive support titanium oxynitride (TiONx) dispersed over carbon-based Ketjen Black and covered by a thin layer of copper (Ir/CuTiONx/C), which gets removed in the preconditioning step. Electrochemical OER activity, stability, and structural changes were compared to the Ir-based catalyst, where Ir nanoparticles without Cu are deposited on the same support (Ir/TiONx/C). To study the effect of the sacrificial less-noble metal layer on the catalytic performance of the synthesized material, characterization methods, namely X-ray powder diffraction, X-ray photoemission spectroscopy, and identical location transmission electron microscopy were employed and complemented with scanning flow cell coupled to an inductively coupled plasma mass spectrometer, which allowed studying the online dissolution during the catalytic reaction. Utilization of these advanced methods revealed that the sacrificial Cu layer positively affects both Ir OER mass activity and its durability, which was assessed via S-number, a recently reported stability metric. Improved activity of Cu analogue was ascribed to the higher surface area of smaller Ir nanoparticles, which are better stabilized through a strong metal-support interaction (SMSI) effect.
CRIS-Team Scopus Importer:2021-10-29
Keywords: identical location transmission electron microscopy (IL-TEM); iridium nanoparticles; oxygen evolution reaction (OER); S-number; titanium oxynitride (TiON) support